POLYMERIC CINCHONA ALKALOIDS FOR THE HETEROGENEOUS CATALYTIC ASYMMETRIC DIHYDROXYLATION OF OLEFINS - THE INFLUENCE OF THE POLYMER BACKBONE POLARITY ON THE COMPATIBILITY BETWEEN POLYMER SUPPORT AND REACTION MEDIUM - SONG, CE; ROH, EJ; LEE, SG; KIM, IO (PERGAMON-ELSEVIER SCIENCE LTD, 1995)
Heterogeneous catalytic asymmetric dihydroxylation of olefins using homo- and co-polymeric cinchona alkaloids has been reported. The benzoate type homopolymers 2a, b showed high enantioselectivity in the heterogeneous ADH reactions, but their catalytic efficiency was largely dependent on the solvent system which may relate to the accessibility of the active catalytic site. The influence of polymer backbone polarity on the compatibility with the reaction medium was investigated using copolymers 3a, b and 4 having polar polymer backbone. The reaction rates and optical yields were dramatically increased by increasing the polarity of the polymer backbone in NMO-acetone/H2O system.
Keywords: R-AMINO-ACIDS; ORGANIC SYNTHESES; HYDRATROPIC ACID; ALKENES; HYDROGENATION; LIGANDS; SCOPE